Nutritional composition and palatability evaluation of some selected commercially available local brown rice in Kelantan prepared by different types of cooking methods - Ting, Chan Chiew (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2013)
Presently, about 2.2 million tons of white rice is consumed by Malaysians every year. Such high white rice intake is associated with type-2 diabetes mellitus (T2DM), dyslipidemia, ischemic stroke and cardiovascular diseases. Brown rice is high nutritional value whole grain. Substituting whole grains including brown rice to white rice is associated with decrease in the risk of T2DM, lowered insulin level and postprandial glucose level. However, brown rice intake is low in Malaysia due to undesirable sensory and texture properties. The present study were conducted to determine nutritional composition and palatability levels of 3 types of brown rice varieties prepared with 3 different cooking methods. Rice samples were either cooked by boiling, simmering or steaming methods and analyzed for moisture, ash, crude fat, crude protein, and carbohydrate content. Sensory evaluation and texture profile analyses were also conducted to assess palatability level of cooked brown rice. Cooked brown rice had 72.82%-78.38% of moisture, 1.42%-2.65% of fat, 0.4 7%-1.44% of ash, 8.05%-9.31% of protein, and 2.67%-4.79% of total dietary fiber (steaming method). These nutritional values were higher than cooked white rice (0.03%-0.08% of fat, 0.11%-0.15% of ash, 6.63%-6.75% of protein, 0.15% of total dietary fiber) (p<0.05) except carbohydrate (10.04%-14.94%) which was lower than cooked white rice (17.75%-28.2%). As compared to boiled brown rice (75.37%- 78.38% of moisture, 0.82%-1.21% of ash, 8.61%-9.31% of protein, 1.42%-2.15% of fat, 10.04%-12.69% of carbohydrate), steamed brown rice contained lower water level (72.82%-73.68%), comparable concentration of ash (1.11%-1.36%) and protein (8.05%-8.92%) but higher fat (2.34%-2.65%) and carbohydrate (13.47%- 14.94%) content. Recent studies reported rice variety, cooking properties such as cooking duration, cooking temperature, water uptake 011 IR) ratio as well as chemical composition of rice like starch, water level and protein contributed to diversity of cooked rice texture. As compared to boiling method, steam cooking produced firmer gelatinized rice of R3 (10.77kg vs 4.22kg) and R4 (11.53kg vs 4.62kg), less sticky R2 (-1.16kg/s vs -0.7lkg/s) and R3 (-1.18kg/s vs -0.56kg/s), more cohesive R2 (5.27kg vs 4.64kg) but less cohesive R4 (3.77kg vs 5.0kg). Optimum hard, less cohesive, less sticky and gummier properties of steamed R2 and R3 achieved significantly higher texture score (4.02 and 3.86) than the boiled one in sensory test (p<0.05). Firmer and less sticky steamed R3 and R4 obtained significant high score in appearance attribute (p<O.OS) compared with boiled one. However, only steamed R3 (4.28) was appeared to be overall preferred than boiled R3 (3.28) (p<O.OS). In sensory evaluation, simmered R4, steamed R3 and R4 were comparable to white rice (p>O.OS) in which white rice was highly accepted by panelists. In summary, different types of cooking methods, chemical composition of rice and rice varieties affected texture and sensory properties of cooked brown rice. Steaming and simmering techniques are recommended methods in cooking brown rice. Medium hard and high fiber brown rice (R3) followed by hard and high fiber brown rice (R4) are recommended as an alternative staple food to replace white rice as they contain higher nutritional composition and comparably palatable as white rice.